Kidney Injury Molecule 1 (KIM-1) as an Early Predictor for Acute Kidney Injury in Post-Cardiopulmonary Bypass (CPB) in Open Heart Surgery Patients - Nora A. Khreba; Mostafa Abdelsalam; A. M. Wahab; Mohammed Sanad; Rania Elhelaly; Mohammed Adel; Ghada El-Kannishy (International Journal of Nephrology)
Introduction. Postoperative acute kidney injury is associated with a higher mortality, a more complicated hospital course with longer hospital stay. Urinary kidney injury molecule 1 may play an important role as an early predictor of acute kidney injury post-cardiopulmonary in open heart surgery. Methods. We evaluated 45 patients who underwent open heart surgery from January 2016 to June 2016. Both urinary kidney injury molecule 1 and serum creatinine were evaluated before operation and 3hs and 24hs after operation. Acute kidney injury was diagnosed according to Kidney Disease: Improving Global Outcomes, 2012 guidelines. Results. In this study, 27 patients developed acute kidney injury. The three hour-post-surgery urinary kidney injury molecule 1 was significantly higher in the acute kidney injury group (P<0.015) and, at the same time, we did not find any significant difference in the serum creatinine levels between the two groups. Conclusion. Although serum creatinine is still the gold standard for diagnosis of acute kidney injury searching for other new markers is mandatory. Urinary kidney injury molecule 1 can be used as simple noninvasive and specific biomarker for early diagnosis of acute kidney injury.